Arsenic Exposure Induces Unscheduled Mitotic S Phase Entry Coupled with Cell Death in Mouse Cortical Astrocytes - Htike, Nang T. T.; Maekawa, Fumihiko; Soutome, Haruka; Sano, Kazuhiro; Maejima, Sho; Aung, Kyaw H.; Tokuda, Masaaki; Tsukahara, Shinji (Frontiers in Neuroscience, 2016)
Abstract There is serious concern about arsenic in the natural environment, which exhibits neurotoxicity and increases the risk of neurodevelopmental disorders. Adverse effects of arsenic have been demonstrated in neurons, but it is not fully understood how arsenic affects other cell types in the brain. In the current study, we examined whether sodium arsenite (NaAsO2) affects the cell cycle, viability, and apoptosis of in vitro-cultured astrocytes isolated from the cerebral cortex of mice. Cultured astrocytes from transgenic mice expressing fluorescent ubiquitination-based cell cycle indicator (Fucci) were subjected to live imaging analysis to assess the effects of NaAsO2 (0, 1, 2, and 4 µM) on the cell cycle and number of cells. Fucci was designed to express monomeric Kusabira Orange2 (mKO2) fused with the ubiquitylation domain of hCdt1, a marker of G1 phase, and monomeric Azami Green (mAG) fused with the ubiquitylation domain of hGem, a marker of S, G2 and M phases. NaAsO2 concentration-dependently decreased the peak levels of the mAG/mKO2 emission ratio when the ratio had reached a peak in astrocytes without NaAsO2 exposure, which was due to attenuating the increase in the mAG-expressing cell number. In contrast, the mAG/mKO2 emission ratio and number of mAG-expressing cells were concentration-dependently increased by NaAsO2 before their peak levels, indicating unscheduled S phase entry. We further examined the fate of cells forced to enter S phase by NaAsO2. We found that most of these cells died up to the end of live imaging. In addition, quantification of the copy number of the glial fibrillary acidic protein gene expressed specifically in astrocytes revealed a concentration-dependent decrease caused by NaAsO2. However, NaAsO2 did not increase the amount of nucleosomes generated from DNA fragmentation and failed to alter the gene expression of molecules relevant to unscheduled S phase entry-coupled apoptosis (p21, p53, E2F1, E2F4, and Gm36566). These findings suggest that NaAsO2 adversely affects the cell cycle and viability of astrocytes by inducing unscheduled S phase entry coupled with cell death that may be caused by mechanisms other than apoptosis.